Field notes contributed by Stephen J. Dinsmore, spring 1997 - Dinsmore, Stephen J.et al (1997)
List of birds and locations contributed by Stephen J. Dinsmore with observers George Brown, Bery Engebretsen, Jim Sinclair and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed